Evaluation of CNC Routed Surface Quality of Maple (Acer pseudoplatanus) and Oak (Quercus robur L.) with Different Milling Angles as Function of Grain Orientation - Antonela Lungu; Lidia Gurău; Camelia Cosereanu (BioResources, 2023)
The study assessed CNC routing quality on maple and oak samples, using 90º V-Grooving router bits at various milling angles as function of grain orientation: 0°, 15°, 30°, 45°, 60°, 75°, 90°, and feed speeds of 3 and 6 m/min at spindle speed of 15,000 rpm. The routing quality was evaluated by roughness parameters for the V flank surfaces and by visual examination for the flanks’ edges. The change in the feed speed had no significant effect for the flanks surface quality of both species, but roughness values were considerable higher for maple samples at 90º and u=3 m/min (Rk = 23.7 µm compared to along the grain, Rk=9.83 µm for u=6 m/min) due to possible processing vibrations. The milling angle as function of grain orientation was significant in the case of oak, as the processing roughness increased with the cutting angle from 0° (Rk=11 to 13 µm) to 60°(Rk =28 to 30 µm). Fuzziness around the earlywood pores of oak was higher for the 6 m/min feed speed. A substantial increase in waviness coinciding with the annual growth areas was measured for crosscut oak samples (Wa = 34.0 µm, compared with Wa =7 .39 µm along the grain). The surface waviness of maple was not sensitive to the variation in the cutting angle or feed speed (Wa was around 3 to 4 µm). For the flank edges, the best visual option was found for cutting along the wood grain and the worst was for 60º, which caused biggest ruptures and especially for the 3 m/min feed speed, for both species.